Examining changes in foreign language educators’ attitudes towards the use of computer-assisted learning - Tamara Oshchepkova; Olesya M. Tolstykh; Ekaterina V. Panasenko; Natalia A. Nazarova; Natalia V. Petrova (Studies in English Language and Education)
As digital technologies continue to permeate all aspects of contemporary society, the educational domain, particularly foreign language teaching, has also significantly transformed. During the 1990s, the introduction of information and communication technologies (ICT) into language teaching was initially met with enthusiasm among educators. However, what originally started as integrating multimedia resources into the learning environment soon escalated into a comprehensive transformation, which included innovations such as online platforms and adaptive learning systems that became part of language teaching curricula. This evolution led to fundamental changes in pedagogical approaches, teacher-student communication, and the overall educational setting within classrooms. As digital technologies evolved and diversified, so did the attitudes of language teachers, whose initial enthusiastic welcome transformed into growing doubt. This research aimed to investigate how digital technologies within the domain of language instruction are utilized and to explore the prevailing attitudes regarding their implementation. The study spanned two decades: the periods from 1990 to 2000 and from 2013 to 2023. Semantic literature analysis of 300 scientific publications was used to determine the educators’ reactions toward the application of ICT, which were categorized into positive, negative, mixed, and research-oriented attitudes. Additionally, a survey of 88 foreign language teachers was conducted to collect empirical data. A clear trend is observed in how language educators perceive and apply technologies in their classrooms. The authors concluded that these tools remain popular among educators despite increasing skepticism and caution regarding ICT efficacy.